2017
DOI: 10.21037/jtd.2017.05.08
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of four-arm robotic lobectomy as solo surgery in patients with clinical stage I lung cancer

Abstract: Background: This study was performed to investigate the feasibility of four-arm robotic lobectomy (FARL) as a solo surgical technique in patients with non-small cell lung cancer (NSCLC). Early outcome and long-term survival of FARL were compared with those of video-assisted thoracoscopic lobectomy (VATL). 87.5%, P=0.386) and disease-free survival (82.5% vs. 75.6%, P=0.589) were comparable.Conclusions: FARL as solo surgery could not be recommended because of safety issues. It required a longer operation time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…The process of literature selection was shown in Figure 1. Totally, 2346 patients underwent RATS, 2553 patients underwent VATS, and 1694 patients underwent open surgery from 32 studies 8,21‐51 (two were prospective and the rest were retrospective studies) who met the eligibility criteria were included. Table 1 showed the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The process of literature selection was shown in Figure 1. Totally, 2346 patients underwent RATS, 2553 patients underwent VATS, and 1694 patients underwent open surgery from 32 studies 8,21‐51 (two were prospective and the rest were retrospective studies) who met the eligibility criteria were included. Table 1 showed the characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…These studies demonstrated RATS may bring comparable clinical outcomes. Several studies showed RATS had the benefit of lower morbidity, mortality, and shorter hospital stay, 7,41,48,60,61 whereas others reported that there were no significant differences 31,34,36,38,39 . Previous meta‐analyses indicated significantly lower morbidity, mortality, and conversion rate in RATS compared with VATS, 9,10,62,63 but no significant differences were observed in operation time, hospital stay, chest tube duration, and lymph nodes extraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the new word "uni-surgeon" is becoming more and more common (5). If we recall the "old fashion" mediastinoscopy and transcervical thymectomy, it is evident that the uni-surgeon already existed year ago and that we are not reinventing the wheel, furthermore other authors already reported their experiences with solo-surgery (6,7). Instead, what is new is that there is enough evidence to say that most of the operations in the chest could be done by a single surgeon with the only help of a telescope and surgical instruments inserted through a single small skin incision or port.…”
mentioning
confidence: 99%
“…Nowadays open thoracic surgery is becoming very rare, and it is therefore very rare that we can teach junior surgeons to perform finger dissection of the main pulmonary artery and veins. Moreover, some studies have shown an higher incidence of vascular problems during RATS (8,9), and it is known that it could be a disaster if the surgeon has no experience in open surgery to control very quickly the main PA.…”
Section: Teaching Rats (And Vats)mentioning
confidence: 99%